Interpretative Repertoires about an Intervention Manual in Early Childhood - Calquin Donoso, Claudia; Guerra Arrau, Rodrigo; Escobar Villalobos, Katherine; Martinez Riquelme, Javier (Política y Sociedad, 2020)
Although governmentality studies have emerged as a relevant theoretical and methodological alternative for studying social policies, few studies have focused on the study of specific policies in childhood. As a way to contribute to research on the relationship between governmentality and childhood, we present the results of research aimed at understanding the interpretative repertoires of a psychosocial care manual for a child protection system in Chile. The methodology consisted of a discursive analysis of the body of the manual based on the perspective of interpretive repertoires. Four repertoires were identified: 1) foundations of all that is social: the relationship as an actor; 2) the state as an agent of national rationality and salvation; 3) the operation of the manual: the state as coach; and finally, 4) the figure of the mother: from the subject at risk to the subject of risk. It is concluded that the discursive production of childhood operates through discursive practices whose function is its depoliticization, under naturalistic interpretive grids that obscure the power, economic and knowledge relations that permeate childhood poverty and the tensions between scientific knowledge and the empirical knowledge of mothers.